Studi Takhrij dan Syarah Hadits Eksistensi Sains Islam - Muhammad Aliansah; Aceng Abdul Kodir (Gunung Djati Conference Series, 2022)
This study aims to discuss the hadith about science. This study uses a qualitative approach with the application of descriptive-analytical methods. The formal object of this research is the science of hadith, while the material object is the discussion of science in the history of Bukhari no. 6223 and No. 6847. The results of this study show that the two hadiths are of hasan li ghairihi quality which meet the qualifications of maqbul ma'mul bih for the practice of Islam. This study concludes the hadith narrated by Bukhari no. 6223 and No. 6847 is relevant for the discussion of Islamic science, such as the theme of yawning and keeping one's mouth shut and avoiding dirty air and the inheritance of traits through genetic engineering explanations.